IMPLEMENTASI KOMPETENSI INTI KURIKULUM 2013 DALAM PEMBELAJARAN SEJARAH (STUDI KASUS DI SMA MTA SURAKARTA) - Permatasari, Leo Agung S., Saiful Bachri, Intan (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
The objectives of research were: 1) to find out the historical teachers? understanding in SMA MTA Surakarta about the main competency of 2013 Curriculum, 2) to find out the implementation plan of main competency of the 2013 curriculum in historical learning in SMA MTA Surakarta, 3) to find out the application of main competency of 2013 curriculum in historical learning in SMA MTA Surakarta, and 4) to find out the evaluation the history teachers took in SMA MTA Surakarta in the implementation of main competency of 2013 curriculum.This study was a descriptive qualitative research. Techniques of collecting data used were interview, observation, and data analysis. To validate the data, the author employed data and method triangulations. Technique of analyzing data used by the author was an interactive model of analysis. The research procedure employed included pre research, field research, data analysis, and report writing stages.The results of research were as follows: 1) History teacher in SMA MTA Surakarta understood the main competency as the foundation on which a teacher realized the objective to be achieved in learning and the objective wanted by curriculum. 2) The plan the teachers made in historical learning implementation with the main competency of 2013 curriculum corresponding to the Learning Implementation Plan (RPP) of 2013 curriculum. 3) The historical learning implementation based on the main competency of 2013 curriculum in SMA MTA Surakarta had run well, because in historical learning process, the teachers always generated spiritual, social attitude competencies, knowledge competency, and skill competency of students. The student had also been able to demonstrate well every main competency. 4) During historical learning process, evaluation on any competency had also been carried out well by the teacher.The conclusion of research was that the application of main competency of 2013 curriculum through scientific approach with 5M (observing, questioning, collecting information, associating, and communicating) stages and student-centered approach could improve the competency of students comprehensively in historical learning in SMA MTA Surakarta.